2007
DOI: 10.1080/02773810701486618
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pulping of Steam‐Exploded Mixed Hardwood Chips

Abstract: We determined the pulping yields for steam-exploded and untreated mixed hardwood chips for kraft pulping processes with and without anthraquinone and/or polysulphide. The pulp yield from steam-exploded chips was 1 -3% lower than from untreated chips under similar conditions. The benefit of kraft pulping with anthraquinone and/or polysulphide was found to be more pronounced for the exploded chips than for the untreated chips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
8
1
Order By: Relevance
“…Also, recent reports have shown that the cooking liquor diffuses more freely into the open structure of exploded chips which leads to easier and shorter kraft pulping (Ahvazi et al, 2007;Martin-Sampedro et al, 2010). Moreover, hemicelluloses removed during the steam explosion pre-treatment can be further converted into value-added products such as ethanol, polymers and other chemicals (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Also, recent reports have shown that the cooking liquor diffuses more freely into the open structure of exploded chips which leads to easier and shorter kraft pulping (Ahvazi et al, 2007;Martin-Sampedro et al, 2010). Moreover, hemicelluloses removed during the steam explosion pre-treatment can be further converted into value-added products such as ethanol, polymers and other chemicals (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…From all these results, it can be concluded that, under the same cooking conditions, the steam exploded chips cooked faster and more efficiently than the untreated chips, or alternatively, they could be pulped at a lower temperature and/or with lower active alkali, while maintaining the same production rate (Ahvazi et al 2007;San Martin 1995;Wafa Al-Dajani et al 2009). With the first option, the cooking time could be reduced, increasing the production rate of the pulp mill.…”
Section: Kraft Pulping Processmentioning
confidence: 92%
“…The most common commercial procedure for extracting hemicelluloses is pre-steaming to release natural wood acids (autohydrolysis) followed by water extraction or acid hydrolysis with small amounts of mineral acids (sulfuric acid or hydrochloric acid). Compared to these processes, steam explosion not only allows the recovery of wood components without their degradation (Avellar and Glasser 1998;Britt 1970), but also leaves a solid residue (exploded chips) that is expected to be pulped more easily than those obtained conventionally due to the open structure of the exploded chips that might encourage an efficient diffusion of cooking liquor into the fibers (Ahvazi et al 2007). Therefore, taking into account the advantages of the steam explosion pretreatment, it can be concluded that this process could be used as an efficient pretreatment in pulping, increasing the total revenue stream for the pulp industry and converting the pulp mill into an integrated forest biorefinery (Ragauskas et al 2006;Van Heiningen 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) were investigated. It has been suggested that the increased porosity and the removal of hemicelluloses increase the accessibility of the pre-treated material (Ahvazi et al 2007;Yang et al 2004). As it can be observed, higher hydrolysis yields were obtained after steam pre-treatment compared to steam explosion pre-treatments.…”
Section: Glucose Yieldsmentioning
confidence: 96%